The walking robots critical position of the kinematics or dynamic systems applied on the environment model - Migdalovici, Marcel; Vladareanu, L; Yu, Hongnian; Pop, N; Iliescu, M; Vladareanu, V; Baran, D; Vladeanu, G (International Journal of Engineering and Technology, 2018)
The exposure is dedicated in the first to mathematical modeling of the environment where the aspects on the walking robots evolution models are described. The environmentâ€™s mathematical model is defined through the models of kinematics or dynamic systems in the general case of systems that depend on parameters. The important property of the dynamic system evolution models that approach the phenomenon from the environment is property of separation between stable and unstable regions from the free parameters domain of the system. Some mathematical conditions that imply the separation of stable regions from the free parameters domain of the system are formulated.Â In the second part is described our idea on walking robot kinematics and dynamic models with aspects exemplified on walking robot leg. An inverse method for identification of possible critical positions of the walking robot leg is established.Â Â